2010
DOI: 10.1111/j.1468-1331.2010.03180.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain immunohistopathological study in a patient with anti-NMDAR encephalitis

Abstract: These findings suggest that the B cells interact with the T cells and are involved in antibody secretion by the plasma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 11 publications
(17 reference statements)
6
66
1
3
Order By: Relevance
“…Consistently, prominent CD138 + plasma cells could be detected in perivascular, and interstitial spaces of a biopsy specimen from another patient with anti‐NMDAR encephalitis (Fig. 1D) 6, 7…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Consistently, prominent CD138 + plasma cells could be detected in perivascular, and interstitial spaces of a biopsy specimen from another patient with anti‐NMDAR encephalitis (Fig. 1D) 6, 7…”
Section: Resultssupporting
confidence: 59%
“…Irrespective of the trigger of anti‐NMDAR encephalitis, data from previous studies suggested an enhancement of the immune response within the CNS, with potential antigen‐driven affinity maturation and clonal expansion of plasma cells 16. This hypothesis was suggested by three findings, (1) a frequent intrathecal synthesis of NMDAR antibodies even early in the disease course,1 (2) biopsy and autopsy material from patients showing brain inflammatory infiltrates containing plasma cells,6, 7 and (3) the better correlation of the course of the disease with CSF antibody titers than with serum antibody titers 5. All four treatment‐naive patients with recent onset anti‐NMDAR encephalitis in the current study showed intrathecal B‐cell and plasma cell accumulation and intrathecal production of NMDAR‐specific IgG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies focusing particularly on the cognitive deficits have shown that there is a long-term morbidity in this disorder, with a good outcome for the patient dependent on early and aggressive treatment (Finke et al 2012). The brains of these patients show few inflammatory cells (mostly T cells) (Tuzun et al 2009;Camdessanche et al 2011;Martinez-Hernandez et al 2011;Bien et al 2012) and magnetic resonance imaging (MRI), and pathological studies show that the neuronal loss in most cases is remarkably mild (Dalmau et al 2007;Iizuka et al 2010;Bien et al 2012). The antibodies have been shown to be pathogenic, at least in vitro.…”
Section: Nmda Receptor (Nmdar) Antibodies Encephalitismentioning
confidence: 99%
“…The immunopathogenesis of this encephalitis is possibly related to antibody immune-responses of B cell and antibody-secreting cells (e.g., plasma cells), which are derived from activated B cells (10)(11)(12). In the present case, normal mouse brain showed immunoreactions to serum samples from this patient, which had been collected after administration of first-line immunotherapy, and before the administration of rituximab.…”
Section: Discussionmentioning
confidence: 55%